2021
DOI: 10.35833/mpce.2019.000136
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Assessment of Impact of Flexible Loads Under Network Tariffs in Low-voltage Distribution Networks

Abstract: Given the historically static nature of low-voltage networks, distribution network companies do not possess the tools for dealing with an increasingly variable demand due to the high penetration of distributed energy resources (DERs). Within this context, this paper proposes a probabilistic framework for tariff design that minimises the impact of DER on network performance, stabilises the revenue of network company, and improves the equity of network cost allocation. To deal with the lack of customers' ' respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In another context, providing ancillary service to the electricity market is recognized as a win-win situation to both the grid and consumers [4], which can be mainly classified into three categories, i.e., demand response (DR) [2]- [4], frequency/voltage support [20], [21], and operation reserve provision [1]. The joint devices in the hydrogen-based microgrid, like electrolyzer and fuel cell, can achieve bi-directional interaction with the grid, which can provide ancillary service to the grid.…”
Section: Nomenclaturementioning
confidence: 99%
“…In another context, providing ancillary service to the electricity market is recognized as a win-win situation to both the grid and consumers [4], which can be mainly classified into three categories, i.e., demand response (DR) [2]- [4], frequency/voltage support [20], [21], and operation reserve provision [1]. The joint devices in the hydrogen-based microgrid, like electrolyzer and fuel cell, can achieve bi-directional interaction with the grid, which can provide ancillary service to the grid.…”
Section: Nomenclaturementioning
confidence: 99%
“…Pimm, Cockerill, and Taylor [16], analyzed Time-of-Use (TOU) tariffs' impact on import and export peaks at the low voltage level but only took into account the reduction in maximum demand at the aggregated level. Azuatalam, Chapman, and Verbič [17], used a probabilistic assessment for two volumetric tariffs and two tariffs with a volumetric and a capacity-based component. The authors concluded that flat tariffs perform better than ToU tariffs for mitigating voltage and alleviating line congestion problems, and the addition of a capacity-based component to such flat tariffs helps to reduce network peaks further.…”
Section: Introductionmentioning
confidence: 99%
“…With a large number of new power equipment such as distributed photovoltaic and electric vehicle charging piles connecting to the low-voltage distribution grid, massive data of power service operations such as demand response [1][2][3][4][5][6], power load management, and remote automatic meter reading services are required to be transmitted, processed, and stored efficiently [7][8][9][10]. However, traditional cloud computing faces problems such as uplink congestion and highlatency transmission since the cloud server is far away from the power distribution grid [11][12], leading to difficulty in meeting the transmission and computing requirements of low-voltage power distribution grid service data [13][14].…”
Section: Introductionmentioning
confidence: 99%